Broken File Retrieval in the Lower Right First Molar Using an Ultrasonic Instrument and Endodontic Micro Forceps - Ratna Meidyawati; Endang Suprastiwi; Hasti Dwi Setiati (Case Reports in Dentistry)
Broken files affect cleaning, shaping, and filling processes of the root canal, thereby causing maintenance failure. Objective. This report explains how to remove broken files using ultrasonic instruments and endodontic micro forceps. Case Report. A 25-year-old female patient had incomplete root canal treatment at the lower right first molar 1 week ago. There were radiolucency in the bifurcation and apical root and the presence of broken files in the 1/3 coronal mesiolingual root. The retrieval started by making a staging platform with an ET20 ultrasonic tip. Endodontic micro forceps were used including a screw wedge that works by clamping the file fragments through a mechanical lock and pulling them to the coronal. Conclusion. It is possible to successfully remove broken files from the root canal using ultrasonic instruments and endodontic micro forceps.